2014
DOI: 10.1111/ijs.12248
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae Infection and Cerebral Infarction Risk: A Meta-Analysis

Abstract: (1) This meta-analysis indicated that C. pneumoniae infection was significantly associated with an increased risk of cerebral infarction. (2) Compared with anti-C. pneumoniae immunoglobulin G, anti-C. pneumoniae immunoglobulin A seemed more effective for predicting the risk of cerebral infarction. (3) No evidence existed that anti-C. pneumoniae-immunoglobulin G detected by enzyme-linked immunosorbent assay could predict the risk of cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
3
1
Order By: Relevance
“…In fact, a significant increase of anti‐ C. pneumoniae antibodies was found in the patients' group, contributing to a two‐fold increase in the risk of stroke. In particular, the IgA seropositivity was significantly higher than IgG in stroke cases, and these results are similar to the findings of recent meta‐analyses . The literature reports a variable stroke risk.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, a significant increase of anti‐ C. pneumoniae antibodies was found in the patients' group, contributing to a two‐fold increase in the risk of stroke. In particular, the IgA seropositivity was significantly higher than IgG in stroke cases, and these results are similar to the findings of recent meta‐analyses . The literature reports a variable stroke risk.…”
Section: Discussionsupporting
confidence: 89%
“…Still, our study found no significant relationship between CVA and IgG and IgM. It could be due to the limitations of our study (24)(25).…”
Section: Discussioncontrasting
confidence: 68%
“…C. pneumoniae is also associated with cerebrovascular disease and cerebral infarction (stroke). A recent meta-analysis suggested that cerebral infarction patients were significantly more likely to be seropositive for C. pneumoniae infection compared to healthy controls (Su and Chen, 2014).…”
Section: Bacterial Pathogens Associated With Neurodegenerationmentioning
confidence: 99%